Tool Interoperability in the Maude Formal Environment (2011)
We present the Maude Formal Environment (MFE), an executable formal specification in Maude within which a user can seamlessly interact with the Maude Termination Tool, the Maude Sufficient Completeness Checker, the Church-Rosser Checker, the Coherence Checker, and the Maude Inductive Theorem Prover. We explain the high-level design decisions behind MFE, give a summarized account of its main features, and illustrate with an example the interoperation of the tools available in its current release.